Targeting Cathepsin Z suppresses endometriosis via the AMPK/mTOR-mediated autophagy and apoptosis axis - Mengjun Zhang; Jialin Wang; Haodi Yue; Zidi Zhang; Lindong Zhang; Xin Zhao (Frontiers in Medicine, 2026)
Background The key biomarkers, therapeutic targets, and pathological mechanisms of endometriosis are urgently needed to be elucidated. The role of CTSZ in EM needs to be clarified, and the potential regulatory mechanisms and corresponding therapeutic drugs of CTSZ need to be explored to demonstrate the feasibility of CTSZ as a biomarker and therapeutic target. Methods Based on transcriptome sequencing of local clinical tissue samples and public data, the key pathogenic gene ( CTSZ ) was screened out using machine learning algorithms (LASSO and SVM-RFE), and the expression of CTSZ was evaluated at multiple levels. The effects of knocking down CTSZ on the proliferation and migration of endometriosis cell lines (12Z) were assessed. The effects of knocking down CTSZ on apoptosis, autophagy and AMPK/mTOR signaling pathways were predicted and investigated. Results CTSZ was found to be abnormally overexpressed in sequencing data, endometriosis clinical tissue samples, and corresponding cell lines (12Z), suggesting it is a potential pathogenic gene. Knockdown of CTSZ significantly inhibited the proliferation and migration of 12Z. CTSZ may be related to key processes and proteins of apoptosis, autophagy and AMPK/mTOR signaling pathways. Knockdown of CTSZ significantly promoted apoptosis and autophagy by activating AMPK and subsequently inhibiting mTOR signaling. Conclusion CTSZ is a potential pathogenic gene and therapeutic target. Its knockdown could activate AMPK and subsequently inhibit mTOR signaling, thereby inducing autophagy and synergistically promoting apoptosis, inhibiting proliferation and migration, and ultimately inhibiting endometriosis.